Robustness Evaluation of Aerodynamic Flutter Stability and Aerostatic Torsional Stability of Long-Span Suspension Bridges - Qing Xia; Yaojun Ge (Applied Sciences, 2023)
Structural robustness is defined by the international engineering community as the capabilities of structural systems that enable them to survive unforeseen or unusual circumstances. In order to highlight the unforeseen and unusual characteristics of wind hazards, this study introduces the concept of structural robustness into the wind-resistant design and evaluation of bridges and proposes the robustness evaluation of aerodynamic flutter and aerostatic torsional stability of long-span bridges. Furthermore, the return period of the design wind speed that a bridge can resist is used to represent wind-resistant robustness. Aiming at the problem of aerodynamic and aerostatic stability, the analysis methods of aerodynamic flutter stability robustness and aerostatic torsional stability robustness of long-span suspension bridges are respectively established. Based on the established methods of aerodynamic flutter stability and aerostatic torsional stability robustness evaluation, robustness analysis is carried out on eight completed long-span suspension bridges and two long-span suspension bridges to be built. The evaluation method proposed in this study makes it possible to measure the ability of bridge structures to resist multiple disasters using the same index.